যদি \(x=a cos\theta + b sin\theta\) এবং \(y=a sin\theta - b cos\theta\) হয় তবে প্রমাণ করো \(x^2+y^2 = a^2+b^2\) ।


\(x^2+y^2=(a cos\theta + b sin\theta)^2+(a sin\theta - b cos\theta)^2\)
বা, \(x^2+y^2=a^2 cos^2\theta +\cancel{2ab sin\theta cos\theta}+ b^2 sin^2\theta\) \(+a^2 sin^2\theta-\cancel{2ab sin\theta cos\theta} + b^2 cos^2\theta\)
বা, \(x^2+y^2=a^2(cos^2\theta + sin^2\theta)\) \(+b^2(sin^2\theta+ cos^2\theta)\)
বা, \(x^2+y^2=a^2\times 1+b^2\times 1\)
বা, \(x^2+y^2=a^2+b^2\) (প্রমানিত)

Similar Questions